2016
DOI: 10.3390/s16122123
|View full text |Cite
|
Sign up to set email alerts
|

Three-Factor User Authentication and Key Agreement Using Elliptic Curve Cryptosystem in Wireless Sensor Networks

Abstract: Secure communication is a significant issue in wireless sensor networks. User authentication and key agreement are essential for providing a secure system, especially in user-oriented mobile services. It is also necessary to protect the identity of each individual in wireless environments to avoid personal privacy concerns. Many authentication and key agreement schemes utilize a smart card in addition to a password to support security functionalities. However, these schemes often fail to provide security along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 31 publications
1
104
0
Order By: Relevance
“…However, in this paper we performed the cryptanalysis of A.K.Das [17] scheme and found that it is susceptible to stolen smart card attack. Similarly, we found that Choi et al [21] (proposed in 2016), Park et al [22] (introduced in 2016), and Moon et al's [23] (proposed in 2017) schemes are also insecure against various security attacks as we have illustrated in Section 4 of this paper.…”
Section: Related Worksupporting
confidence: 63%
See 3 more Smart Citations
“…However, in this paper we performed the cryptanalysis of A.K.Das [17] scheme and found that it is susceptible to stolen smart card attack. Similarly, we found that Choi et al [21] (proposed in 2016), Park et al [22] (introduced in 2016), and Moon et al's [23] (proposed in 2017) schemes are also insecure against various security attacks as we have illustrated in Section 4 of this paper.…”
Section: Related Worksupporting
confidence: 63%
“…Park et al [22] performed the security analysis of Chang et al's [29] scheme. Then, Park et al proposed an improved scheme of user authentication using the fuzzy extractor and biometric information in order to provide forward secrecy, accurate password update phase and resist off-line password guessing attacks.…”
Section: Review Of Park Et Al's Schemementioning
confidence: 99%
See 2 more Smart Citations
“…YoHan Park et al [33] implemented technique as Biometric based user authentication and key agreement. It is based on ECC.…”
Section: Related Workmentioning
confidence: 99%